2008
DOI: 10.1021/jf801002w
|View full text |Cite
|
Sign up to set email alerts
|

Metal Content and Physicochemical Parameters Used as Quality Criteria in Virgin Argan Oil: Influence of the Extraction Method

Abstract: Metal content was determined in 26 samples of virgin argan oil from Morocco. An ETA-AAS with previous sample dilution with MIBK technique was used. In oil obtained by traditional method, Fe ranged from 0.8 to 4.0 mg/kg, Cu from 160.4 to 695.7 microg/kg, Cr from 10.3 to 55.3 microg/kg, Mn from 18.1 to 70.8 microg/kg, and Pb from 28.5 to 450.0 microg/kg. In oil obtained by a half-industrialized method, Fe ranged from 0.8 to 1.7 mg/kg, Cu from 158.4 to 385.0 microg/kg, Cr from 10.0 to 48.1 microg/kg, Mn from 15.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…We also evidenced the necessary elimination of goat-peeled argan fruit from the oil preparative process [9,10]. Finally, it has been shown that argan oil prepared from mechanically pressed kernels presents a better profile than hand-pressed oil, in terms of chemical composition [11,12], taste, and preservation [9,12]. Argan kernel roasting also deserves attention because it induces pleasant hazelnut aroma and taste that transfer to the oil during extraction [10].…”
Section: Introductionmentioning
confidence: 68%
“…We also evidenced the necessary elimination of goat-peeled argan fruit from the oil preparative process [9,10]. Finally, it has been shown that argan oil prepared from mechanically pressed kernels presents a better profile than hand-pressed oil, in terms of chemical composition [11,12], taste, and preservation [9,12]. Argan kernel roasting also deserves attention because it induces pleasant hazelnut aroma and taste that transfer to the oil during extraction [10].…”
Section: Introductionmentioning
confidence: 68%
“…In order to check the quality and appropriate conservation of the oil samples, the acid value (expressed as percentage of oleic acid), the peroxide index (expressed as milli-equivalents of active oxygen per kg of oil) and the K 270 extinction coefficient (calculated from absorption at 270 nm using a Perkin-Elmer Lambda 25 UV/VIS spectrophotometer, Waltham, Massachusetts, USA) were measured, following the analytical methods of the Commission of the European Communities (2003) as described elsewhere (Marfil et al, 2008).…”
Section: Samplesmentioning
confidence: 99%
“…Unsaturated lipids are particularly susceptible to oxidation during processing and storage via autoxidation and photosensitized oxidation (Marfil et al 2008).…”
Section: Changes In Fatty Acids Compositionmentioning
confidence: 99%